THE EFFECT OF LEARNING MANAGEMENT ON STUDENTS’ LEARNING OUTCOMES IN ACCOUNTING EDUCATION - Rolia Wahasusmiah (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
This study examines the effect of learning management on students’ learning outcomes in accounting education at Politeknik Prasetiya Mandiri PSDKU Palembang. A quantitative approach with an explanatory research design was employed. The sample consisted of 50 accounting students selected using purposive sampling. Data were collected through a structured questionnaire to measure learning management, covering planning, implementation, and evaluation, and documentation of students’ academic results to measure learning outcomes. The data were analyzed using descriptive statistics and simple linear regression. The results indicate that learning management has a significant positive effect on students’ learning outcomes. The coefficient of determination indicates that learning management explains a substantial portion of the variance in students’ academic achievement. These findings suggest that effective learning management plays an important role in improving students’ learning outcomes in accounting education. Therefore, strengthening lecturers’ learning management competencies is recommended to enhance the quality of teaching and learning processes.